Direct somatic embryogenesis and plant regeneration in Garcinia indica Choiss - Thengane, Shubhada Ratnakar; Deodhar, Swapna R.; Bhosle, S. V.; Rawal, S. K. (Current Science, 2006)
Direct somatic embryogenesis without an intervening callus phase was induced from immature seeds of Gar- cinia indica Choiss. Woody plant medium supplemented with 6-benzyl amino purine (BAP) (4.44-22.19 mu m) alone or in combination with a-naphthaleneacetic acid (2.69 mu m) produces somatic embryos within a period of 2-3 weeks with 80% frequency. Embryo induction was observed all over the explant surface. Origin of the embryo was confirmed histologically from sub-epidermal layer of the seed. Maturation of these embryos was achieved after 12 weeks of culture on a medium containing BAP (16.08 mu m) in combination with indole-3-acetic acid (2.85-5.71 mu m) and/or kinetin (4.65 mu m). About 75% of the regenerated somatic embryos germinated into complete plantlets. The plantlets were acclimatized successfully with 92% survival in greenhouse.
Keywords: Garcinia indica; guttifereae; seeds; somatic embryos